Automatic Generation of Stippling Illustrations from two Photographs - Germán Arroyo; Domingo Martín; M. Victoria Luzón (Virtual Archaeology Review, 2012)
In this paper we present a software tool that is able to reconstruct the depth field of the objects from two photographs and to obtain a pseudo 3D model. Using this information our system is able to difference background from foreground, and therefore, what are the interesting elements in the photographs and stipple them in different ways. This tool needs almost no user interaction. The user simply has to align both photographs and indicate the level of detail according to the distance. The rest is decided by our software. Whereas a professional illustrator needs more than 20 hours to finish a similar illustration, our software is able to do it in just few seconds.